Building a Robotics at School Project with Social Transformation - Gomes, Luciana Oliveira de Souza; Pinto, Igor Nicoletti; Taira, Bruno Yoshihara; Nicio, Gustavo Yudi Sagara; Campi, João Carlos Tonon; Pereira, Mateus José Prado; Macedo, Tábata Rodrigues Do Prado; Barbosa, Yago Mariano; Aroca, Rafael Vidal; Ogashawara, Osmar; Hernandes, André Carmona; Pazelli, Tatiana F. P. A. Taveira (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2021: Anais do XIII Simpósio Brasileiro de Robótica e XVIII Simpósio Latino Americano de Robótica, 2021)
This article discusses the process of designing and implementing an educational robotics project applied by members of the Red Dragons robotics team, founded at Universidade Federal de Sao Carlos (UFSCar). This report involves the discovery of the need to apply innovative methodologies in Brazilian public schools, going through the process of instructor training to the structuring of classes that make up a robotics course, including adaptations for virtual and hybrid learning in the pandemic scenario.